Effect of targeting treatment of mitomycin C immunoconjugate on stomach neoplasm - Chen Ling-Ji; Zhang Su-Yin; Zhang Jia-Liu; Zhang Zhou; Li Song; Chen Min; Zhang Xue-Yong; Chen Xi-Tao (Acta Pharmacologica Sinica, 2016)
An anti-gastric cancer monoclonal antibody MGb2-mitomycin C conjugate via dextran T-70 as intermediate (MGb2-PAD-MMC) was produced, and 28-30 g molecules of MMC were introduced into 1 g molecule of MGb2. Ninety-six hours after ip of 125I-MGb2-PAD-MMC (1.48 MBq/22 micrograms MGb2 per mouse) to nude mice bearing human gastric cancer SGC-7901, the tumor tissue:blood (T/NT) radioactivity ratio was 2.6, very much higher than that of the control 125I-normal IgG-PAD-MMC group (T/NT = 0.20). Single photo computed tomography imaging confirmed the results of biodistribution study. MGb2-PAD-MMC exhibited selective killing action on the SGC-7901 cells in vitro, which was considered to be mediated by monoclonal antibody MGb2. Nude mice inoculated with SGC-7901 xenograft in bilateral subrenal capsule were treated by MMC (ip), human recombinant interferon-alpha (Hu-IFN-alpha im), MGb2-PAD-MMC (ip) and MGb2-PAD-MMC+Hu-IFN-alpha daily for 5 d beginning 4 h after inoculation. The efficacy of the reagents estimated by the reduction of tumor size and calculated by T/C (%), was 28.3%, 16.4%, 47.8%, and 83.1%, respectively. These results demonstrated that the antitumor effect of MGb2-PAD-MMC was superior to free MMC, and that the Hu-IFN-alpha might further enhance the action of MGb2-PAD-MMC.